Post-Traumatic Stress and World Assumptions: The Effects of Religious Coping - Zukerman, Gil (Journal of religion and health, 2014)
Religiosity has been shown to moderate the negative effects of traumatic event experiences. The current study was deigned to examine the relationship between post-traumatic stress (PTS) following traumatic event exposure; world assumptions defined as basic cognitive schemas regarding the world; and self and religious coping conceptualized as drawing on religious beliefs and practices for understanding and dealing with life stressors. This study examined 777 Israeli undergraduate students who completed several questionnaires which sampled individual world assumptions and religious coping in addition to measuring PTS, as manifested by the PTSD check list. Results indicate that positive religious coping was significantly associated with more positive world assumptions, while negative religious coping was significantly associated with more negative world assumptions. Additionally, negative world assumptions were significantly associated with more avoidance symptoms, while reporting higher rates of traumatic event exposure was significantly associated with more hyper-arousal. These findings suggest that religious-related cognitive schemas directly affect world assumptions by creating protective shields that may prevent the negative effects of confronting an extreme negative experience.